IMPLEMENTASI PEMIKIRAN EKONOMI MUHAMMAD BAQIR ASH SADR DI MASA PANDEMI COVID-19 - Rahila Amanatul Ummah; Siti Nur Azizah (Universitas Muhammadiyah Prof Dr Hamka, 2022)
One of the main ideas of Muhammad Baqir ash Sadr's economics is the responsibility of the government in the economic field. The COVID-19 pandemic has resulted in considerable changes in Indonesia. Even descriptive analysis has shown that this pandemic has caused supply and demand side problems in the Indonesian economy, a sharp decline in Indonesia's economic growth from around 5 percent to around 2 percent per year. This research is classified as Library research, where he conducts an in-depth understanding of research in the form of journals and other forms related to Baqr Ash Sadr's thoughts on government responsibility in the economic field. The existence of this policy is proof that the correlation between Baqr Ash Sadr's thoughts and the current reality is still relevant, that government intervention is in the form of wealth distribution which is realized in various programs with the aim of prospering the community in accordance with Baqr Ash Sadr's thoughts, regarding social security, distribution wealth and government intervention, in this case to do with the economy. Keywords: Social security, social balance and COVID-19.